TEACHING ENGLISH SELF INTRODUCTION THROUGH CHARACTER BUILDING- BASED MATERIAL - Hafidza Nash’ul Amrina (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2015)
The important of inserting character building on English material has been realized by the government. There are many ways of doing that and one of them is through inserting culture on language teaching. Self introduction is one of the important materials that should be taught. Therefore it is needed to make self introduction material based on character building. This article discusses teaching English self introduction through character building-based material.